2009
DOI: 10.1149/1.3202664
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Single-beam Megasonic System for Nano-particle Cleaning

Abstract: A single-beam megasonic system for nano-particle cleaning which less likely cause nano-pattern damage was designed. Considering ultrasonic wave propagation, a length of quartz waveguide was decided at a uniform acoustic wave region. The anti-resonance frequency of the piezoelectric actuator was measured to be 987 kHz, which agreed well with the fabricated quartz waveguide operating frequency of 983 kHz. The acoustic pressure of the single-beam megasonic system was measured, and the averaged value increased by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
(4 reference statements)
0
2
0
Order By: Relevance
“…3. From lateral-force AFM measurements it was found that these structures are appropriate for damage tests (7). We also used gate stack lines composed of an SiO 2 hardmask on top of poly-crystalline silicon deposited on top of SiON with an aspect ratio ~ 4 (W/H/S = 40/160/1000nm) for comparison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. From lateral-force AFM measurements it was found that these structures are appropriate for damage tests (7). We also used gate stack lines composed of an SiO 2 hardmask on top of poly-crystalline silicon deposited on top of SiON with an aspect ratio ~ 4 (W/H/S = 40/160/1000nm) for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…Two experimental datapoints obtained with gate stack lines as damage test structures and 78nm silica particles were also added for comparison and show better damage/cleaning performance as they are lying closer to the lower-right corner of the graph. This means that a-Si lines are much more fragile, probably due to the weaker a-Si/SiO 2 interface compared to the poly-Si/SiON interface (7). Customized damage/cleaning windows can be obtained by setting specifications on the damage density and particle removal efficiency.…”
Section: Trade Off Between Damage Generation and Particle Removal: Ph...mentioning
confidence: 99%